Comparing Calcium Alginate Dressings to Vacuum-assisted Closure: A Clinical Trial - Vassallo, Ian Mario; Formosa, Cynthia (Wounds (King of Prussia, Pa.), 2015)
Several treatment modalities and protocols for arterial wound ulcers are available; however, little consensus exists on which treatment modality provides the best results. The present study sought to compare and evaluate the clinical efficacy of vacuum-assisted closure wound therapy to calcium alginate dressings in the treatment of neuroischemic diabetic foot ulceration. A single-center quasi-experimental matched subject clinical trial was conducted on 30 subjects living with type 2 diabetes and presenting with a newly diagnosed neuroischemic foot ulceration. Subjects were divided into 2 groups. Group A (n = 15) underwent negative pressure wound therapy and Group B (n =15) underwent treatment using calcium alginate dressings. Ulcer area and depth were measured during the trial. Both negative pressure therapy and calcium alginate dressings were effective in reducing the surface area and depth of ulcers (P = 0.0001). However, negative pressure was 3.2 times more effective in reducing surface area and 3.78 times more effective in reducing depth of ulcers when compared to calcium alginate (P = 0.0001). Vacuum-assisted closure should be considered as the treatment of choice for neuroischemic ulceration owing to its advantages in reducing surface area and depth when compared to calcium alginate dressings. Improved care could result in improved health outcomes, improved quality of life, and fewer diabetes-related foot complications.